Carbon Nanotubes Effect for Polymer Materials on Break Down Voltage - Loai S. Nasrat; Berlanty A. Iskander; Marina N. Kamel (Institute of Advanced Engineering and Science, 2017)
Epoxy resin composites reinforced to different types of carbon nano-particles have been fabricated. Carbon black (20, 30 and 40 wt. %), graphene (0.5 to 4 wt. %) and carbon nanotubes (CNT) (0.5 to 2 wt. %) were added with different weight percentages to epoxy. The dielectric strength of composites was tested in several conditions such as (dry, wet, low salinity and high salinity). The mechanical characterization showed that the nano-composite Polymer enhanced by using these particles in the tensile strength. Thermal gravimetric analysis shows effect of these nano-particles on the thermal structure of epoxy resin. Scanning Electron Microscopic test is used to characterize the dispersion of carbon nano-particles and to analysis the fractured parts in the nano scale.